The Accuracy of the Qibla Axis (Inhiraf al-Qibla): A Legal Debate - Kahera, Akel Ismail (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Accuracy of the Qibla Axis (Inhiraf al-Qibla): A Legal Debate